BRD4: New hope in the battle against glioblastoma - Weichen Duan; Miao Yu; Jiajia Chen (Elsevier, 2023)
The BET family proteins, comprising BRD2, BRD3 and BRD4, represent epigenetic readers of acetylated histone marks that play pleiotropic roles in the tumorigenesis and growth of multiple human malignancies, including glioblastoma (GBM). A growing body of investigation has proven BET proteins as valuable therapeutic targets for cancer treatment. Recently, several BRD4 inhibitors and degraders have been reported to successfully suppress GBM in preclinical and clinical studies. However, the precise role and mechanism of BRD4 in the pathogenesis of GBM have not been fully elucidated or summarized. This review focuses on summarizing the roles and mechanisms of BRD4 in the context of the initiation and development of GBM. In addition, several BRD4 inhibitors have been evaluated for therapeutic purposes as monotherapy or in combination with chemotherapy, radiotherapy, and immune therapies. Here, we provide a critical appraisal of studies evaluating various BRD4 inhibitors and degraders as novel treatment strategies against GBM.